Análisis de rendimiento de estrategias de asignación de recursos para servicios con tráficos a ráfagas. - Romero, Ana Rosa; De la Bandera Cascales, Isabel; Outes-Carnero, José; Mendo, Adriano; Ramiro, Juan; Barco-Moreno, Raquel (My University, 2023)
The percentage of bursty traffic in the network is currently increasing. To avoid problems derived from this, such as occasional overloads in the network or inefficiency in the allocation of resources, the role of the scheduler is essential and differentiating for the best possible performance of the network. To analyze this situation, a system level simulator has been used with a bursty traffic model with on-off states and Proportional Fair Minimum Rate scheduler. Bursty traffic has been tested with different activity factors and the scheduler has been configured with different scheduling strategies to achieve different degrees of fairness and to observe the impact on the results.
Keywords: Telecomunicaciones; Tráfico a ráfagas; Scheduler; Proportional Fair; On-Off; Rendimiento